Global marketing strategies - Jeannet, Jean-Pierre.; Hennessey, H. David (Boston : Houghton Mifflin, 1998)
This book is divided into five parts: Understanding the Global marketing environment; Analyzing global marketing opportunities; Developing global marketing strategies; Designing global marketing programs; and Managing the global marketing effort.
Keywords: Management; Export marketing; Export marketing -- Management; Export marketing -- Management -- Case studies